2018
DOI: 10.2754/avb201887040387
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of Czech and Mānuka honey on selected mastitis pathogens

Abstract: The work is focused on the antibacterial effect of four types of blossom honey, one honeydew and two Mānuka honey (MAN100+ and MAN400+) on selected pathogenic microorganisms isolated from cow’s milk (Staphylococcus aureus 51 and S. aureus 428), sheep’s milk (S. aureus 627), and from the Czech Collection of Microorganisms (Streptococcus uberis CCM 4617, Streptococcus agalactiae CCM 6187, Enterococcus faecalis CCM 4224 and Escherichia coli CCM 4787). The concentrations of honey samples were 20% and 30%. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…These strains were capable of inhibiting S. aureus growth; besides, the results revealed that S. aureus was the most sensitive of all tested microorganisms. The study of Klimešová et al (2018) confirms that S. aureus is sensitive to antibacterial substances in the environment. Baran et al (2017) evaluated the influence of temperature on SE production in cheeses maturing at 4 and 12 °C.…”
Section: Discussionsupporting
confidence: 52%
“…These strains were capable of inhibiting S. aureus growth; besides, the results revealed that S. aureus was the most sensitive of all tested microorganisms. The study of Klimešová et al (2018) confirms that S. aureus is sensitive to antibacterial substances in the environment. Baran et al (2017) evaluated the influence of temperature on SE production in cheeses maturing at 4 and 12 °C.…”
Section: Discussionsupporting
confidence: 52%